2020
DOI: 10.5194/esurf-8-51-2020
|View full text |Cite
|
Sign up to set email alerts
|

Stabilising large grains in self-forming steep channels

Abstract: Abstract. It is understood that the interaction between sediment supply and discharge drives first-order behaviour of alluvial deposits. The influence of the grain size distribution over the mobility and resultant evolution is, however, unclear. Four experiments were conducted in a scaled physical model for two grain size distributions, analogous to a one-dimensional self-formed alluvial fan. We demonstrate the unsuitability of the median grain size as a predictor of deposit behaviour at flows when the materia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
2
8
0
Order By: Relevance
“…Circled points represent the first measurement taken during each phase largely inherited as the increase in shear stress was not sufficient to entrain larger-than-average grains located at bar-heads. This is consistent with studies that have identified larger-than-average grains controlling sediment transport and thresholds for channel deformation, rather than the average grain size (Booker & Eaton, 2020;MacKenzie & Eaton, 2017;MacKenzie et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Circled points represent the first measurement taken during each phase largely inherited as the increase in shear stress was not sufficient to entrain larger-than-average grains located at bar-heads. This is consistent with studies that have identified larger-than-average grains controlling sediment transport and thresholds for channel deformation, rather than the average grain size (Booker & Eaton, 2020;MacKenzie & Eaton, 2017;MacKenzie et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Preliminary tests by Hamilton et al (2013) showed that using a more widely graded mixture produced channels that appeared more "realistic". Similarly, experiments by Booker and Eaton (2020), conducted in a narrow flume designed to represent the aggrading conditions on fans, demonstrated that a narrowly graded mixture failed to reproduce the morphodynamics of a widely graded mixture with the same D 50 . In addition, recent studies have highlighted how the largest grains in a distribution, while often only a small fraction of that distribution, have a disproportionately large influence on channel morphodynamics (MacKenzie and Eaton, 2017;MacKenzie et al, 2018;Williams et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, experiments by Booker and Eaton (2020), conducted in a narrow flume designed to represent the aggrading conditions on fans, demonstrated that a narrowly graded mixture failed to reproduce the morphodynamics of a widely graded mixture with the same D 50 . In addition, recent studies have highlighted how the largest grains in a distribution, while often only a small fraction of that distribution, have a disproportionately large influence on channel morphodynamics (MacKenzie & Eaton, 2017;MacKenzie et al, 2018;Williams et al, 2019).…”
mentioning
confidence: 95%